Auditing: an instructional manual for accounting students - Millichamp, A.H. (London: DP Publications Ltd, 1990)
This manual provides a simplified but thorough approach to the understanding of modern auditing theory and practice. It takes account of all the auditing standards and guidelines issued to date, all the statements of standard accounting practice issued to date and the Companies Act 1989.
The Educational Low-Priced Books Scheme (ELBS) edition.
Includes index
rua 17/10/16
Loans
Keywords: Auditing